Estudo e mapeamento de campos eletromagnéticos, na faixa de 60 hz, em uma subestação de alta tensão e em linhas de transmissão de 230 kv - Figueiredo, Ana Luiza de (Universidade Federal Rural do Semi-Árido, 2019)
To meet the growing demand for electricity, brazilian transmission systems have been expanded and increasingly it is common to find high voltage transmission lines and substations along the urban layout. At the same time, there is a concern from the scientific community regarding the level of exposure to electromagnetic fields and possible effects on human health, which are subject to individuals who transit, reside or work around these electric power enterprises. Therefore, this work aims to study the distribution of electromagnetic fields within a 230 kV / 69 kV step-down substation, which operates in the extremely low frequency range (ELF), at 60 Hz, as well as in the 230 kV transmission lines that preceding this substation, in the city of Mossoró - RN. For this purpose, on-site measurements of the intensity of the electric fields and magnetic fields using an inductive and free space isotropic characteristics meter in the 60 Hz central frequency range, were performed near the substation equipment and in the easement range of the transmission lines, in previously established points, respecting the height, directions and orientations of the main norms and literature of the area, in national and international scope. The results obtained during the measurements were later applied in the Golden Surfer® software, with the purpose of exposing the spatial distribution through contour maps, to facilitate the understanding and visualization of the most intense places of electric and magnetic fields and their behavior around the equipment and generally within the substation in question and along the transmission line. These maps were developed using interpolation techniques and statistical validations, which allowed to obtain satisfactory results, through the data behavior. Finally, the measured and interpolated values were compared with those established by the renowned regulatory standards and guidelines to determine if the maximum exposure levels in this region are within safe limits of the electric and magnetic field
Keywords: Campo Elétrico; Campo Magnético; Subestações de Energia; Linhas de Transmissão; Exposição Eletromagnética; Electric Field; Magnetic field; Power substation; Transmission lines; Electromagnetic exposure; ENGENHARIAS::ENGENHARIA ELETRICA